Infant observation : the first year of life - Gering, Jeanne (Rhodes University, Faculty of Humanities, Department of Psychology)
This research project is about infant-observation, that is looking at, observing, and studying parent-infant interactions and relationships within the first year of life. The principle intention of the study is to illustrate and shed light upon human infant development and how the newborn becomes a fully functioning member within the family. The study provides a context in which to consider parent-infant interaction beginning in utero, expanding to the birthing process, and continuing through the infant's first year. It focuses on specific themes of parent-infant interaction. The following situations are explored: the role of the mother; the mother as a container; the infant's experience of containment; the internalisation of experience; the symbolic meaning of food; dealing with distress and the development of concrete communication; the growth of a sense of ego; and, the infant's internal world. The study concludes by addressing various implications for further psychotherapy and compares the therapist-client relationship to the mother-infant relationship. The research outlines one particular psychoanalytic theoretical orientation of mental and emotional development. It is a model derived predominantly from The Developmental School Theorists and Object Relations Theorists, namely, Bowlby, Klein, Mahler and Winnicott. This model looks at the infant's earliest relationships and the processes these set up within the infant's developing mind. Infant observation, asa research method proposed by Bick and Sidoli, links method and theory, and serves as the methodological approach utilised in the present study. A video, based on the parent-infant interaction of three families, provides observational data and may be viewed in conjunction with this research.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Infant psychology; Parent and infant; Interpersonal communication in infants; Mother and infant